Achados macroscópicos de Tuberculose em abatedouros Frigoríficos: Revisção sistemática e metanálise - Bárbara Vanelli Rocha Couto (2021)
Bovine tuberculosis (BTB) is a zoonosis caused by the microorganism Mycobacterium bovis, which affects cattle, buffaloes and other domestic and wild mammals. Tuberculosis transmission among cattle occurs mainly by air, inhaling infected droplets from coughing or nasal secretions, or by consuming contaminated feed and water. The lesions resulting from contamination by M. bovis in cattle are predominantly distributed in the respiratory tract and in the associated lymph nodes, as this is the main entry point for the microorganism in animals. In order to guarantee the sanitary quality in obtaining the meat, a post mortem inspection is carried out in the slaughterhouses, which consists of an accurate examination of the carcass, parts of the carcasses, viscera and lymph nodes in order to identify the presence of possible anatomopathological changes. As it is a zoonosis of great importance to public health, the official veterinary inspection service establishes judgment criteria for carcasses and parts of carcasses, organs and viscera of slaughtered animals, ranging from conditional use to condemnation, according to with the extent of the lesions. This study aimed to carry out a systematic review, followed by a meta-analysis, of the studies already carried out on the prevalence of macroscopic findings of bovine tuberculosis in slaughterhouses. The articles were retrieved through a systematic search in five electronic databases (PubMed/MEDLINE, Scopus, Virtual Health Library, Scielo and Google Scholar). A total of 1342 articles were found and 10 were selected through the eligibility criteria. Through the statistical analyzes performed, the I2 was calculated at 100%, being considered high. Due to the high heterogeneity, the fixed effect model was used for the calculation. The global prevalence found of 0.25% is significant, which further increases the concern related to the lack of case notification and the need to discard positive animals. Thus, more studies should be carried out on the disease, contributing to its eradication.